2016
DOI: 10.7763/ijesd.2016.v7.799
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Utilization of the Earthworms Eisenia fetida and Eisenia andrei for the Disposal of Polymers

Abstract: Abstract-Disposing plastics has been an incredibly arduous task. Many of the plastics that people use take tens of hundreds of years to decompose. Yet, plastic usage increases year by year. Plastics have actually become a part of people's lives, from water bottles to the exterior of televisions. To eliminate the usage of plastics would be impossible. Therefore, methods for effectively disposing plastics are necessary. However, the existing models are rather too inefficient or are too expensive. To incinerate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…For example, earthworms, the most abundant annelids in soils globally 75 , play a critical role in soil nutrient recycling because their ingestion of decaying material breaks down organic matter and fertilizes soils 76 . While our understanding of the earthworms ability to degrade bioplastics is still in its infancy 77,78 , one encouraging result is that earthworms can partially degrade the bioplastic polylactic acid 79 . Although they are not able to fully degrade polylactic acid to CO2 80 , our discovery that earthworms, as well as other soil inhabitants like insects, have PHADs indicates that these animals may be able to contribute to the full degradation of PHA-based plastics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, earthworms, the most abundant annelids in soils globally 75 , play a critical role in soil nutrient recycling because their ingestion of decaying material breaks down organic matter and fertilizes soils 76 . While our understanding of the earthworms ability to degrade bioplastics is still in its infancy 77,78 , one encouraging result is that earthworms can partially degrade the bioplastic polylactic acid 79 . Although they are not able to fully degrade polylactic acid to CO2 80 , our discovery that earthworms, as well as other soil inhabitants like insects, have PHADs indicates that these animals may be able to contribute to the full degradation of PHA-based plastics.…”
Section: Discussionmentioning
confidence: 99%
“…The sanitary pads consisted of cotton, layers of polyethylene, adhesives, synthetic fibers, etc. Similarly, the diapers consist of cellulose, polyethylene, and a super absorbent polymer, as well as tapes, elastics, and other adhesive materials, which take a long time to biodegrade [6,7]. The morphological study of Eisenia fetida was carried out using a wax dissection box by crude method.…”
Section: Methodsmentioning
confidence: 99%
“…Polymer degradation is defined as any change in physical or chemical properties caused by environmental factors, such as light, heat, and moisture, as well as biological activity [ 14 ]. However, few studies have shown the physical changes in the microplastics and ingestion of microplastics due to earthworm activities [ 15 , 16 , 17 , 18 ].…”
Section: Role Of Earthworms In Physical and Chemical Degradation Of P...mentioning
confidence: 99%
“…Earthworms’ ( Eisenia Foetida and Eisenia Andrei ) consumption of five plastic types has resulted in a mass reduction, and polyethene, nylon, polypropylene, ethylene–vinyl acetate, and linear low-density polyethene were among the polymer powders studied [ 18 ]. Even though the study found a decrease in polymer mass, it is possible that this was unrelated to earthworm digestion.…”
Section: Role Of Earthworms In Physical and Chemical Degradation Of P...mentioning
confidence: 99%